2016
DOI: 10.1177/1078345815618200
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Psychological Health and Subjective Well-Being Among Incarcerated Individuals With Serious Mental Illness

Abstract: While improving the psychological health and well-being of individuals with serious mental illness can help reduce emotional distress and increase resilience, not enough is known about the well-being of incarcerated individuals with mental illness. Using the Schwartz Outcome Scale-10, the authors examined changes in subjective well-being and its association with other clinical symptoms and personality features in 43 mentally ill inmates in a large jail. All participants demonstrated significant improvement in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…That is to say, in the low level of GWB, resilience can significantly predict mental health, and in the higher level of GWB of nurses, resilience cannot significantly predict mental health. It is probably because people with low GWB may effectively play the role of resilience and better adaptation to ever‐changing environment (Leidenfrost, Calabrese, Schoelerman, et al, ). When one can handle the negative life events, get rid of the adversity, and return to the previous situation, then one can reduce the generation of mental health problems.…”
Section: Discussionmentioning
confidence: 99%
“…That is to say, in the low level of GWB, resilience can significantly predict mental health, and in the higher level of GWB of nurses, resilience cannot significantly predict mental health. It is probably because people with low GWB may effectively play the role of resilience and better adaptation to ever‐changing environment (Leidenfrost, Calabrese, Schoelerman, et al, ). When one can handle the negative life events, get rid of the adversity, and return to the previous situation, then one can reduce the generation of mental health problems.…”
Section: Discussionmentioning
confidence: 99%
“…Psychometric analysis of this scale has demonstrated good reliability and validity in both clinical and nonclinical settings among adults and adolescents (10,15,(18)(19)(20). Also, its psychometric features make it a noteworthy measure due to its generality, promptness and ease of administration and scoring (7,14,(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…studied subjective wellbeing and psychological health among 43 people with serious mental illness in a New York prison, using the Schwartz Outcome Scale-10. 26 Neither study reported comparative data or population norms or examined associations between mental wellbeing and demographic or custodial characteristics.…”
Section: Discussionmentioning
confidence: 99%
“… 23 , 24 The only studies to date which measure mental wellbeing appear to be limited to small subgroups of people in prison, such as specific ethnic groups 25 or those with serious mental illness. 26 …”
Section: Introductionmentioning
confidence: 99%